Assessment of endothelial function during the loading phase of infliximab in psoriasis: a potential predictor of its drug survival. (31st August 2018) - Nakao, Momoko; Nakamura, Kouki; Fukasawa, Takemichi; Shida, Rino; Ito, Arisa; Ichimura, Yohei; Takahashi, Takehiro; Mitsui, Aya; Yoshizaki, Ayumi; Shibata, Sayaka; Kamata, Masahiro; Araki, Mayuko; et al.
Abstract: Background: Tumor necrosis factor inhibitors decrease the risk of cardiovascular events in moderate to severe psoriasis, but the association between their effects on endothelial function and those on skin lesions has not been well studied. We investigated the association between infliximab effects on endothelial function during the loading phase and those on skin lesions in patients with psoriasis. Methods: We evaluated endothelial function with reactive hyperemia‐peripheral arterial tonometry index (RHI) in 15 patients with psoriasis before the first and third infusions of infliximab. Patients were stratified into two groups; those who maintained Psoriasis Area and Severity Index (PASI) 75 response for more than 6 months (defined as responders) and the others (defined as nonresponders). Results: Six weeks after the initiation of infliximab (before the third infusion), PASI scores were significantly improved compared with baseline, while RHI values were not altered in the whole patient group. However, when the responders and the nonresponders were analyzed separately, RHI values tended to be decreased before the third infusion compared with baseline in the nonresponders, while being unchanged in the responders. Importantly, the difference in ∆RHI reached a statistical significance between the two groups, and the cutoff value (mean − 2 standard deviation of RHI values in the responders) identified the nonresponders with 67% of sensitivity and 100% of specificity. Conclusions: The decrease in RHI values before the third infusion may serve as a predictor for the long‐term unfavorable effect of infliximab on psoriatic skin lesions.